2020
DOI: 10.3390/biom10030431
|View full text |Cite
|
Sign up to set email alerts
|

Rings, Hexagons, Petals, and Dipolar Moment Sink-Sources: The Fanciful Behavior of Water around Cyclodextrin Complexes

Abstract: The basket-like geometry of cyclodextrins (CDs), with a cavity able to host hydrophobic groups, makes these molecules well suited for a large number of fundamental and industrial applications. Most of the established CD-based applications rely on trial and error studies, often ignoring key information at the atomic level that could be employed to design new products and to optimize their use. Computational simulations are well suited to fill this gap, especially in the case of CD systems due to their low numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…The simulation parameters are similar to those employed in previous works for similar systems [25,26]. All the simulations were performed using the GROMOS 54a7 force field [27] (Schmid, et al 2011) with SPC water molecules [28] and the GROMACS 2020 engine [29,30].…”
Section: General Simulation Methodsmentioning
confidence: 99%
“…The simulation parameters are similar to those employed in previous works for similar systems [25,26]. All the simulations were performed using the GROMOS 54a7 force field [27] (Schmid, et al 2011) with SPC water molecules [28] and the GROMACS 2020 engine [29,30].…”
Section: General Simulation Methodsmentioning
confidence: 99%
“…The role of SBECD is to improve both the solubility and stability of remdesivir via inclusion complex formation ( Pipkin et al, 2020 ). Molecular dynamic study proved the interaction between remdesivir and SBECD of various DS ( Garrido et al, 2020 ; Piñeiro et al, 2021 , Piñeiro et al, 2022 ). Recent NMR investigations suggested that the protonation state of the aminopyrrolo-triazine moiety of remdesivir can play a key role in the cyclodextrin-remdesivir interaction ( Várnai et al, 2022 ).…”
Section: Introductionmentioning
confidence: 90%
“…Less explored even is the effect of such interactions on the properties and distribution of water molecules—the main component of said emulsions. In the work of Garrido et al, the behavior of water molecules around (α-CD) 2 ·SDS (SDS denotes sodium dodecyl sulfate) was simulated, showing fast dynamics of hydrogen bonding [ 2 ]. Water molecules are distributed around the units of the complex in symmetric choreographies, as if the water molecules themselves were synchronized swimmers: they form a hexagon around the apolar water-exclusion area of the mid-transversal section of the α-CD ring, and, at the rims, hexasymmetric, flowerlike contact areas with the host.…”
Section: Fundamental Research: the Water Ballet And The Cyclodextrin mentioning
confidence: 99%